Cardiac Rehabilitation to Prevent Rehospitalization in Myocardial Infarction Patients - Diah Ivana; Cholid Tri Tjahjono (Universitas Brawijaya, 2022)
Introduction. There is mounting evidence that cardiac rehabilitation (CR) based on physical activity has a positive influence on the degree of disability and level of quality of life, in addition to playing an important and beneficial role in modifying morbidity and mortality. Discussion. Patients who have experienced an acute myocardial infarction, are candidates for cardiac rehabilitation as an essential component of their care. Clinical evaluation, optimization of pharmacotherapy, physical training, psychological rehabilitation, evaluation and reduction of coronary disease risk factors, lifestyle modification, and patient education are the components that should be included in comprehensive cardiac rehabilitation. Immediately following the acute phase of a myocardial infarction, the designated team (consisting of a physician, physiotherapist, nurse, psychologist, dietician, and social worker) should begin comprehensive cardiac rehabilitation. This rehabilitation should contain individualized programs that are designed to optimize the patient's physical, psychological, social, and emotional status. It is recommended that the modern model of comprehensive cardiac rehabilitation be started as soon as possible, continued for the required amount of time, properly staged, and individualized depending on the clinical status of the patients. Conclusion. Cardiac rehabilitation after myocardial infarction is an exercise method that could improve the post myocardial infarct patient’s living quality, includes increasing cardiac ejection fraction, exercise tolerance, and physical status. Therefore, it can decrease rate of rehospitalization in patient post myocardial infarct.